Os professores homens no magistério público primário de Mato Grosso (1937-1945) : uma análise sobre as masculinidades - Gomes, Crystyne Silva de Matos (2019)
During the Estado Novo (1935-1947) the Brazilian population was immersed in changes in the political, social, economic and cultural context in Brazil. Men and women were subjected to outlining new social ways to live in the country. Directed by the New State, a policy of unification and centralization, authoritarian that aimed to extend control of the federal government and limit as much as possible the influences of regional oligarchies. The regime began to define new patterns of coexistence and conduct, building in the country a new representation of what it was to be a man, a citizen of the Estado Novo. In the educational context in Mato Grosso, there were a large number of primary schools and in them teachers men who dedicated their lives to the exercise of primary teaching in that region. Within this context the research has as general objective, Understanding the teaching profession in Mato Grosso in the light of the theoretical reference of Masculinities. Besides the specific objectives: To contextualize the Hegemonic Masculinity of the period; Understand the teacher's obligations in the Primary Public Magisterium in Mato Grosso; Identify the men who made a career in the primary public teaching in Mato Grosso during the Estado Novo period and which were the Subaltern Masculinities produced by the primary male teachers. The relevance of this research is found in the contributions to the history of Brazilian and Mato Grosso education, about the primary male teaching work since the subject has been little problematized, to understand how the men exercised the primary teaching and created our forms of masculinities contributes to the opening of our historiographic paths on teaching and gender representations. In this way, the object of this research is based on Masculinities (CONNEL, 1987), involved in the actions and practices of male teachers who study in public primary schools in the State of Mato Grosso during the Estado Novo period (1937-1945). It is based on the perspective of Cultural History (CHARTIER, 1991) because it considers that history is told and reconstructed in diverse cultural opportunities, whether they are in the writing of daily facts, in the artistic productions and in the insurrections of memory. The methodological itinerary used is based on the qualitative analysis of the historical approach, based on printed and handwritten documentary sources, located in the National Library (digital archive), Public Archive of Mato Grosso (APMT) and in the collections of the Research Group History of Education and Memory GEM) of the Federal University of Mato Grosso (UFMT). It was also used the oral memory resource of students who experienced teaching together with teachers who practice teaching public primary in the delimited period, published by other researchers. The partial results point out that the actions and social practices of men who dedicated themselves to the primary public magisterium created Masculinidades Subalternas a Hegemonic Masculinity constructed by the regime of Getúlio Vargas. There was an expected behavior to be realities for men throughout the period linked to wage earning, family headship and the modernization of the Country. The work in primary teaching developed by men, created several new forms of masculinities identified as subaltern.